Multipotent stem cells of mother's milk - Alessandra Reali; Melania Puddu; Maria Cristina Pintus; Maria Antonietta Marcialis; Giuseppina Pichiri; Pierpaolo Coni; Danila Manus; Angelica Dessì; Gavino Faa; Vassilios Fanos (Hygeia Press di Corridori Marinella, 2016)
In recent years the presence of stem cells (hBSCs: human breastmilk-derived stem cells) and epithelial progenitors has been demonstrated in mother's milk (MM). Stem cells present in samples of fresh MM exhibit a high degree of vitality and this makes possible the performance of cell cultures and to evaluate the differentiation capacity of the hBSCs. The most important datum that expresses the enormous potential of the use of MM stem cells is the presence of a cell population capable of differentiating into the three mesoderm, endoderm and ectoderm lines. The small number of studies and MM samples analyzed and the different sampling methods applied suggest standardization in the collection, analysis and culture of MM in future studies, in consideration of the well-known extreme variability of MM composition, also from the standpoint of cells. The analysis of literature data confirms the uniqueness of MM and its enormous potential. Proceedings of the 2nd International Course on Perinatal Pathology (part of the 11th International Workshop on Neonatology · October 26th-31st, 2015) · Cagliari (Italy) · October 31st, 2015 · Stem cells: present and future Guest Editors: Gavino Faa, Vassilios Fanos, Antonio Giordano